Fe-Based Metal Organic Frameworks (Fe-MOFs) for Bio-Related Applications - Rongyue Zhu; Mengru Cai; Tingting Fu; Dongge Yin; Hulinyue Peng; Shilang Liao; Yuji Du; Jiahui Kong; Jian Ni; Xingbin Yin (MDPI AG, 2023)
Metal-organic frameworks (MOFs) are porous materials composed of metal ions and organic ligands. Due to their large surface area, easy modification, and good biocompatibility, MOFs are often used in bio-related fields. Fe-based metal-organic frameworks (Fe-MOFs), as important types of MOF, are favored by biomedical researchers for their advantages, such as low toxicity, good stability, high drug-loading capacity, and flexible structure. Fe-MOFs are diverse and widely used. Many new Fe-MOFs have appeared in recent years, with new modification methods and innovative design ideas, leading to the transformation of Fe-MOFs from single-mode therapy to multi-mode therapy. In this paper, the therapeutic principles, classification, characteristics, preparation methods, surface modification, and applications of Fe-MOFs in recent years are reviewed to understand the development trends and existing problems in Fe-MOFs, with the view to provide new ideas and directions for future research.